Study on the Immunomodulatory effect of Qixian Decoction in an Asthmatic Mice Model Based on Serum Metabolomics - Manman Li; Qingge Chen; Zhenhua Ni; Xinyi Le; Tong Wu (Georg Thieme Verlag KG, 2024)
The study aimed to investigate the immunomodulatory effect of Qixian Decoction (QXT) in an asthmatic model. In this study, ovalbumin (OVA)-induced asthma in female SPF BALB/c mice was established. Mice were randomly divided into four groups (n = 8): a control group, an OVA model group, a low-dose Qixian Granules (KLL) group, and a high-dose Qixian Granules (KLH) group. Mice in the KLL and KLH groups were given the Qixian Granules at a dose of 8 and 16 g/kg, respectively. After the treatment, the lung pathology was evaluated. The expression of inflammatory factors was determined. Serum metabolomics was used to investigate the overall regulation of QXT on the metabolism of asthmatic mice. Our data showed that QXT significantly increased the expression levels of Th1-related interferon-γ, Treg-related interleukin (IL)-10, and transforming growth factor-β1 while decreasing Th1-related tumor necrosis factor α levels in bronchoalveolar lavage fluid, and Th2-related IL-4 and IL-5 levels in serum when compared with the model group (all p < 0.05). Serum metabolomics revealed 28 potential biomarkers associated with nine pathways. Compared with the control group, 19 different metabolites in the KLL group and 18 different metabolites in the KLH were reversed. QXT's therapeutic effect against asthma might be related to glycerophospholipid metabolism and arachidonic acid metabolism. In conclusion, QXT could ameliorate inflammation of the OVA-induced asthmatic mice, mainly by regulating the expression of immune-related factors, probably through regulating the Th1/Th2 immune balance and promoting the proliferation of Treg.